2010
DOI: 10.2139/ssrn.1815070
|View full text |Cite
|
Sign up to set email alerts
|

Language Knowledge and Earnings in Catalonia

Abstract: This paper represents the first contribution that investigates the economic value of Catalan knowledge in terms of earnings, focusing on national and foreign first-and second-generation immigrants in Catalonia. Specifically, drawing on data from the "Survey on Living Conditions and Habits of the Catalan Population (2006)", we want to quantify the expected earnings differential between individuals who are proficient in Catalan and those who are not, taking into account the potential endogeneity between knowledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 26 publications
1
21
1
Order By: Relevance
“…Our main finding of a wage penalty for dialect speaking is seemingly at odds with existing literature on the effect of being bilingual which suggests that there is a wage premium for being proficient in a second language (Christofides and Swidinsky 2010;Di Paolo and Raymond 2012;Chen et al 2014;Cappellari and Di Paolo 2018). However, there is a clear distinction between speaking an additional language and speaking a dialect.…”
Section: How To Explain Our Findings?contrasting
confidence: 84%
See 1 more Smart Citation
“…Our main finding of a wage penalty for dialect speaking is seemingly at odds with existing literature on the effect of being bilingual which suggests that there is a wage premium for being proficient in a second language (Christofides and Swidinsky 2010;Di Paolo and Raymond 2012;Chen et al 2014;Cappellari and Di Paolo 2018). However, there is a clear distinction between speaking an additional language and speaking a dialect.…”
Section: How To Explain Our Findings?contrasting
confidence: 84%
“…Previous studies have focused on the effect of language proficiency on earnings of male immigrants. Recent examples are Bleakley and Chin (2004), Miranda and Zhu (2013a, b), Di Paolo and Raymond (2012) and Yao and van Ours (2015). However, it is not only language proficiency that affects labor market performance.…”
Section: Introductionmentioning
confidence: 99%
“…In Catalonia, some economists have recently shown that, ceteris paribus, those who are fluent in Catalan find jobs more easily, obtain promotions more quickly and earn more than those who are not fluent in Catalan (Rendon 2007;Di Paolo and Raymond 2010).…”
Section: Social Mobility and Language: Paradoxes And Causality Problemsmentioning
confidence: 99%
“…8 To verify the admissibility of these instruments, we perform a test for overidentification (Hansen's J test) based on the two-stage least squares (TSLS) estimator. According to Di Paolo and Raymond (2012) and Cameron and Trivedi (2010), the endogenous switching model and the TSLS estimator are similar methods for addressing an endogenous dummy variable (irrigation, in our case). Thus, we used TSLS to understand whether the chosen instruments are valid.…”
Section: Resultsmentioning
confidence: 98%